Design and implementation of a dynamic deployment based on heterogeneous processor - Qian Hongwen; Chen Guangwei (Dianzi Jishu Yingyong)
Aiming at the real-time switching and flexible intelligent invocation requirements of various life services supported by satellites, a scheme for real-time, efficient and dynamic switching and deployment of processor functions is designed based on the heterogeneous processor of wireless wide-area signal services. Through the customization of multiple functions of large-resource FPGA and multi-chip 8-core DSP combined with dynamic deployment design, real-time dynamic reconfigurable processor system functions are realized, and five types of FPGA are combined with two types of DSP applications to dynamically combine control, data links, and complete multi-task intelligent switching.